Academic Hardiness And Social Support: Universitas Terbuka Student’s Case - Ernayanti Nur Widhi; Siti Khumaidatul Umaroh; Rusna Ristasa (Journal on Education, 2023)
This study examines whether there are differences in academic hardiness between Indonesia Open University students who join Pokjar and those who do not join Pokjar. Pokjar is an abbreviation of “study group” which consists of a group of students and is managed by several administrators. Students who choose to take distance learning are scattered in different areas and do not meet each other in the same class. When problems occur related to the learning process, students ask questions and seek information through existing communication channels. Pokjar is a group of students who build commitment and mutual agreement to help each other and support each other smoothly and successfully study at the Indonesia Open University with or without the facilities of other parties. Pokjar management is needed to help provide administrative services and information about the Open University to students who need it. In the perspective of open and distance education, Pokjar can be positioned as a form of social support where students can convey all their problems to Pokjar, and Pokjar will help solve these problems to the University. This study uses an academic hardiness questionnaire which was compiled based on aspects of academic toughness by Benishek (2004) and modified by the researcher. The research sample was 705 Open University students from various study programs. After the difference test was conducted, it was found that there was a significant difference between students who attended Pokjar and students who did not take Pokjar. The average academic toughness score of students who joined Pokjar (Mean = 144.16) was higher than students who did not join Pokjar (Mean = 139.44). Research on social support for academic hardiness is often done, a new finding in this study is that in distance learning, social support can come from Pokjar. We carried out further investigations using FGDs and deep interviews to find out what kind of social support we received from the Pokjar. The type of social support felt by students when they joined the Pokjar was in the form of companionship support, namely support that includes the availability of groups to spend time together. This support causes a person to feel that he is part of a group where members can share with each other.